Principal Leadership As A Friend In Developing Teachers' Pedagogical Competence In Elementary Schools - Bensi, Ekarista Indriani Wahyuni; Kuswandi, Dedi; Muksar, Makbul (UNIVERSITAS PAKUAN, 2025)
The quality of basic education is highly dependent on teachers' ability to manage learning effectively. However, many teachers still face difficulties in mastering these skills, resulting in suboptimal pedagogical competence. This condition emphasizes the importance of the principal's role. Until now, hierarchical and administrative leadership patterns have caused the relationship between principals and teachers to be less than warm. Therefore, more humanistic and collaborative leadership is needed, namely principals as friends. This study aims to describe: (1) how principals implement a friend-based leadership approach in elementary schools, (2) supporting factors that influence the application of principal leadership as a friend in developing teachers’ pedagogical competence in elementary schools, (3) obstacles/constraints faced by principals in developing teachers’ pedagogical competence in elementary schools, (4) Strategies of principal leadership as a friend in efforts to enhance teachers’ pedagogical competence in elementary schools. This study uses a qualitative approach with a multi-case study design. Data were collected through passive participatory observation, structured interviews, and documentation. Analysis was conducted through single case and cross-case analysis. The results show that the principal's leadership as a friend is manifested through a humanistic, open, and collaborative approach without neglecting professional boundaries. This approach creates a harmonious working atmosphere and motivates teachers to develop their pedagogical competencies. Supporting factors include shared commitment, collaboration between principals, teachers, and parents, support from the education office, and a culture of learning together. The obstacles that arise include limited time, facilities, funds, and teacher readiness. To overcome this, the principal implements strategies such as training, mentoring, sharing good practices, supervision, appreciation, and an empathetic approach. These strategies have been proven to strengthen professional relationships and improve the pedagogical competence of teachers in elementary schools.